2021
DOI: 10.3390/sym13060978
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Heat Engines with Singular Interactions

Abstract: By harnessing quantum phenomena, quantum devices have the potential to outperform their classical counterparts. Here, we examine using wave function symmetry as a resource to enhance the performance of a quantum Otto engine. Previous work has shown that a bosonic working medium can yield better performance than a fermionic medium. We expand upon this work by incorporating a singular interaction that allows the effective symmetry to be tuned between the bosonic and fermionic limits. In this framework, the parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…Further work has investigated the power and EMP of Otto cycles using working mediums with polynomial fundamental relations (e.g. photonic gases) 140 , two-level working mediums 37,141 , degenerate quantum gas working mediums 142 , quantum statistics 105,109,110 , and Bose-Einstein condensate working mediums 108 . The power and EMP of other cycle types has also been examined, including Carnot cycles with two-level quantum systems as a working medium 143 , and a uniquely quantum cycle consisting of isoenergetic, isothermal, and adiabatic strokes 127,128 .…”
Section: B Endoreversiblity and Finite Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Further work has investigated the power and EMP of Otto cycles using working mediums with polynomial fundamental relations (e.g. photonic gases) 140 , two-level working mediums 37,141 , degenerate quantum gas working mediums 142 , quantum statistics 105,109,110 , and Bose-Einstein condensate working mediums 108 . The power and EMP of other cycle types has also been examined, including Carnot cycles with two-level quantum systems as a working medium 143 , and a uniquely quantum cycle consisting of isoenergetic, isothermal, and adiabatic strokes 127,128 .…”
Section: B Endoreversiblity and Finite Powermentioning
confidence: 99%
“…The quantum Otto cycle has been examined in a huge variety of contexts including, but not limited to, implementations with working mediums of single spin systems 37,99,100 , coupled spin systems 77,101,102 , harmonic oscillators [103][104][105] , relativistic oscillators 106 , an ideal Bose gas 107 , a Bose-Einstein condensate 108 , anyons 109,110 , a two-level atom 111 , coupled spin-3/2 biquartits 112 , and an NI 2 dimer 113 . Furthermore, it has been shown that the cycle performance can be enhanced with a "quantum afterburner" 114 (as elaborated on in Sec.…”
Section: Quantum Otto Enginesmentioning
confidence: 99%
“…with k B and T being the Boltzmann constant and temperature, respectively. In this case, ρ A becomes a canonical density matrix of the Gibbsian state that is a perfectly decoherent state with no off-diagonal elements in the energy eigenbasis (see References [13,14] and the works cited therein). In other words, B is regarded as the heat reservoir.…”
Section: Nonuniqueness Of Decoherence Channelmentioning
confidence: 99%
“…The standard Otto engine is a quasi-static cycle (which means there is always thermodynamic equilibrium) that considers two isochoric and two adiabatic processes [ 14 , 15 , 16 , 17 , 25 , 26 ]. In our case, the isochoric stages are replaced by constant magnetic field processes.…”
Section: Otto Enginementioning
confidence: 99%
“…The Otto cycle, widely used by the automotive industry, is today one of the most studied cycles theoretically and experimentally in thermodynamics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. This is due to two fundamental reasons: The first is that the efficiency depends on the properties of the working substance, and the second is that its execution stages separate the contributions of work and heat [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%